Preparation method of monodisperse doped titanium dioxide with in-situ lattice strain

By introducing homologous titanium sources and low-valence metal ion doping during the preparation of titanium dioxide, combined with surface modification, and in-situ control of lattice strain, the problem of limited oxygen vacancy control was solved, and the preparation of monodisperse and high-transparency composite materials of titanium dioxide was realized.

CN119263343AActive Publication Date: 2025-01-07ZHEJIANG UNIV +2
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411592073.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-07
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

In the current technology for preparing titanium dioxide, the ability to regulate oxygen vacancies is limited, leading to particle agglomeration, which affects the transparency and mechanical properties of the material, making it difficult to achieve high-quality monodispersity.

Method used

By introducing a homologous titanium source a second time, the lattice strain at the interface is controlled in situ by utilizing the difference in lattice shrinkage between the amorphous and crystalline states. With the addition of low-valence metal ion doping and surface modifiers, monodisperse doped titanium dioxide with in situ lattice strain is prepared.

Benefits of technology

This method achieves monodispersity and abundant oxygen vacancies in titanium dioxide, preserving the original surface structure and properties, and constructs a high-transparency composite functional material, avoiding the particle agglomeration problem caused by calcination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263343A_ABST
    Figure CN119263343A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of monodisperse doped titanium dioxide with in-situ lattice strain, and belongs to the field of preparation of nano functional material dispersions. The titanium dioxide prepared by the method has abundant oxygen vacancies and surface active sites. According to the method, a titanium source is injected twice, a rapid heating solvothermal reaction is carried out, lattice strain regulation and control are achieved through lattice shrinkage rate difference at an amorphous and crystal interface, oxygen vacancy forming energy is reduced, and an oxygen vacancy structure is further stabilized through doping of low-valence metal ions. And the surface modifier can regulate and control the surface properties of the particles to adapt to various solvent systems, so that a high-transparency composite functional material is conveniently prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano-functional material dispersion preparation; more specifically, to a method for preparing monodisperse doped titanium dioxide with in-situ lattice strain. Background Art

[0002] In recent years, titanium dioxide (TiO2) has been widely used in semiconductors, coatings, photovoltaics, medicine, and displays due to its excellent and stable physical and chemical properties, low cost, and non-toxicity. Its intrinsic surface properties and electronic structure have also been widely studied. Oxygen vacancies, as an extremely common defect, play a pivotal role in regulating the surface properties and electronic structure of titanium dioxide. Therefore, regulating the content of oxygen vacancies in titanium dioxide will be of great significance for its practical application.

[0003] Oxygen vacancies can usually be obtained by calcining titanium dioxide under vacuum or reducing atmosphere, and a large number of studies have been conducted on blue / black titanium dioxide obtained by this method. However, this usually leads to the consumption of organic groups on the surface of titanium dioxide particles and severe agglomeration between particles. Titanium dioxide is difficult to be monodispersed in solvents with high quality. If it is used as a filler to construct a composite material, it will seriously affect the transparency and mechanical properties of the material.

[0004] In-situ construction of oxygen vacancies during the preparation of titanium dioxide to avoid subsequent calcination will greatly improve its potential and performance in subsequent applications. Low-valent metal ion doping and anion doping are common methods for in-situ construction of oxygen vacancies, which have been widely studied and applied, but their doping ratios are usually limited by lattice stability, resulting in limited ability to regulate oxygen vacancies. Reducing the oxygen vacancy formation energy through lattice strain and thus efficiently modulating the content of oxygen vacancies is a novel and effective solution. In the preparation of titanium dioxide, based on the difference in lattice shrinkage between the amorphous and crystalline states, the lattice strain at the interface is in-situ regulated by secondary introduction of a homologous titanium source. On the one hand, the content of oxygen vacancies will be effectively regulated, and on the other hand, the original surface structure and properties of titanium dioxide will be retained, which is beneficial to subsequent surface modification and the construction of highly transparent composite materials. In addition, the use of low-valent metal ions as dopants is beneficial to further reduce the oxygen vacancy formation energy and stabilize the oxygen-rich vacancy structure according to charge balance. Therefore, it is of great significance to design and develop a simple preparation method for monodisperse doped titanium dioxide with in-situ lattice strain. On the one hand, it provides a new synthetic idea for realizing titanium dioxide lattice strain, and on the other hand, it provides a material basis for the development of new titanium dioxide composite materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing monodisperse doped titanium dioxide with in-situ lattice strain, wherein the prepared nano titanium dioxide has both monodispersity and abundant oxygen vacancies. By introducing a homologous titanium source for the second time, the lattice strain at the interface is regulated in situ by relying on the difference in lattice shrinkage between the amorphous and crystalline states, which will effectively regulate the content of oxygen vacancies on the one hand, and retain the original surface structure and properties of titanium dioxide on the other hand, and achieve monodispersity of titanium dioxide after surface modification and construct a high-transparency composite functional material.

[0006] Based on this, the present invention mainly adopts the following technical solution, a method for preparing monodisperse doped titanium dioxide with in-situ lattice strain, which comprises the following steps:

[0007] 1) preparing a precursor solution of doped nano-titanium dioxide by aging and performing a first solvothermal reaction;

[0008] 2) After the first solvothermal reaction is completed, the reaction solution is cooled, a titanium source is added thereto, and then the temperature is raised to carry out a second solvothermal reaction, and lattice strain is generated in situ by utilizing the difference in lattice shrinkage rate at the crystal-amorphous interface;

[0009] 3) The reaction product is subjected to multiple precipitation centrifugation and washing, and the surface is modified using a surface modifier to obtain the monodisperse doped titanium dioxide with in-situ lattice strain.

[0010] Wherein, the precursor solution in step 1) comprises an organic solvent, water, a doping metal salt, a titanium source and a hydrolysis inhibitor;

[0011] Wherein, the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, pentanol, hexanol, heptanol, octanol, dodecanol, ethylene glycol, propylene glycol, hexylene glycol, benzyl alcohol, phenylethyl alcohol;

[0012] Wherein, the doping metal salt is selected from one or more of the following substances: lithium chloride, sodium chloride, potassium chloride, rubidium chloride, magnesium chloride, barium chloride, copper chloride, manganese chloride, ferric chloride, zinc chloride, tin chloride, aluminum chloride, lithium nitrate, sodium nitrate, potassium nitrate, rubidium nitrate, magnesium nitrate, barium nitrate, copper nitrate, manganese nitrate, ferric nitrate, zinc nitrate, tin nitrate, cerium nitrate, europium nitrate, aluminum nitrate, lanthanum nitrate, terbium nitrate and samarium nitrate;

[0013] Wherein, the titanium source is selected from one or more of the following substances: titanium tetrachloride, titanyl sulfate, titanium acetylacetonate, tetraethyl titanate, tetrabutyl titanate, isopropyl titanate, titanic acid and metatitanic acid;

[0014] Wherein, the hydrolysis inhibitor is selected from one or more of the following substances: formic acid, acetic acid, propionic acid, butyric acid, lactic acid, citric acid, tartaric acid, salicylic acid, nitric acid, hydrochloric acid and sulfuric acid.

[0015] In the precursor solution, relative to the organic solvent, the addition amount of the doped metal salt is 0.001-0.03 g / mL, the addition amount of the titanium source is 0.08-0.8 g / mL, and the addition amount of the hydrolysis inhibitor is 0.001-0.05 g / mL; in the precursor solution, the mass ratio of water to the titanium source is 0.02-0.7.

[0016] The first solvothermal reaction temperature in step 1) is 100-230°C, the first solvothermal reaction pressure is 0.01-5Mpa, and the first solvothermal reaction time is 0.5-72h; preferably, the first solvothermal reaction temperature is 140-220°C, the first solvothermal reaction pressure is 0.1-3Mpa, and the first solvothermal reaction time is 1-48h; more preferably, the first solvothermal reaction temperature is 160-200°C, the first solvothermal reaction pressure is 0.1-2Mpa, and the first solvothermal reaction time is 2-24h.

[0017] The titanium source described in step 2) is selected from one or more of the following substances: titanium tetrachloride, titanyl sulfate, titanium acetylacetonate, tetraethyl titanate, tetrabutyl titanate, isopropyl titanate, titanic acid and metatitanic acid; preferably, the titanium source described in step 2) is the same type of titanium source as that in step 1).

[0018] The molar ratio of the amount of the titanium source added in step 2) to the amount of the titanium source in the precursor solution in step 1) is 0.05-1.

[0019] Preferably, in step 2), while adding the titanium source, an appropriate amount of water is also added to the reaction solution, wherein the molar ratio of the added water to the added titanium source is 0.01-1; preferably, the molar ratio of water to the added titanium source is 0.05-0.8; more preferably, the molar ratio of water to the added titanium source is 0.1-0.6;

[0020] Wherein, the second solvent thermal reaction temperature is 200-400°C, the second solvent thermal reaction pressure is 0.01-5Mpa, and the second solvent thermal reaction time is 0.5-24h; preferably, the second solvent thermal reaction temperature is 220-350°C, the second solvent thermal reaction pressure is 0.1-3Mpa, and the second solvent thermal reaction time is 0.75-12h; more preferably, the second solvent thermal reaction temperature is 260-320°C, the second solvent thermal reaction pressure is 0.1-2Mpa, and the second solvent thermal reaction time is 1-6h.

[0021] Wherein, the second solvent thermal reaction needs to heat up quickly and keep warm after reaching the desired reaction temperature, and the heating rate is 20-100°C / min; preferably, the heating rate is 25-80°C / min; more preferably, the heating rate is 30-60°C / min.

[0022] Wherein, the surface modifier described in step 3) includes one or more of titanate, phosphate, organic acid and silane coupling agent;

[0023] Wherein, the titanate is selected from one or more of the following substances: isopropyl tri(dodecylbenzenesulfonyl) titanate, isopropyl triisostearate titanate, bis(acetylacetonato) diisopropyl titanate, isopropyl tri(dioctylphosphoyloxy) titanate, isopropyl dioleyloxy (dioctylphosphoyloxy) titanate, di(octylphenol polyoxyethylene ether) phosphite and tetraisopropyl di(dioctylphosphite) titanate;

[0024] Wherein, the phosphate ester is selected from one or more of the following substances: 4-hydroxybutyl dihydrogen phosphate, 2-ethylhexyl dihydrogen phosphate, 9-octadecene-1-ol phosphate, isooctyl phosphate, dodecyl phosphate, tetradecyl phosphate, lauryl alcohol polyoxyethylene ether phosphate and tridecyl polyoxyethylene ether phosphate;

[0025] The organic acid is selected from one or more of the following substances: butyric acid, lactic acid, citric acid, tartaric acid, salicylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, oleic acid, linoleic acid, lauric acid, tetradecanedioic acid, octadecanedioic acid and eicosanedioic acid;

[0026] Wherein, the silane coupling agent is selected from one or more of the following substances: vinyl trimethoxysilane, vinyl triethoxysilane, octyl trimethoxysilane, octyl triethoxysilane, dodecyl trimethoxysilane, dodecyl triethoxysilane, hexadecyl trimethoxysilane, hexadecyl triethoxysilane, 3-(acryloxy) propyl trimethoxysilane, phenyl trimethoxysilane, γ-aminopropyl trimethoxysilane, 3-glycidyl ether oxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, N-β-aminoethyl-γ-aminopropyl triethoxysilane, methoxytriethylene glycol ether propyl trimethoxysilane, 11-mercapto undecyl trimethoxysilane, 3-mercaptopropyl trimethoxysilane and diethylphosphoethyl triethoxysilane.

[0027] Wherein, the centrifugal speed described in step 3) is 3000-8000r / min; preferably, the centrifugal speed is 4000-7000r / min; more preferably, the centrifugal speed is 5000-6000r / min.

[0028] Wherein, the washing solvent is selected from one or more of the following substances: ethanol, acetone, tetrahydrofuran, propylene glycol methyl ether acetate, toluene and heptane.

[0029] Preferably, the surface modification process in step 3) is: adding the washed product and the surface modifier to a reaction solvent to carry out a surface modification reaction.

[0030] The reaction temperature of the surface modification process is 25-150°C, and the reaction time is 0.5-24h; preferably, the reaction temperature is 50-130°C, and the reaction time is 1-12h; more preferably, the reaction temperature is 80-120°C, and the reaction time is 2-8h;

[0031] The mass ratio of the surface modifier to the washed product is 0.05-1;

[0032] Wherein, the reaction solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, pentanol, hexanol, heptanol, octanol, dodecanol, ethylene glycol, propylene glycol, hexylene glycol, benzyl alcohol, acetone, butanone, propylene glycol methyl ether acetate, tetrahydrofuran, dimethyl sulfoxide, dichloromethane, chloroform, ethyl acetate, butyl acetate, benzene, toluene, xylene, heptane, n-hexane, cyclohexane and petroleum ether.

[0033] The doped titanium dioxide obtained by the present invention can be monodispersed in a dispersing solvent, and the dispersing solvent can be selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, pentanol, hexanol, heptanol, octanol, dodecanol, ethylene glycol, propylene glycol, hexylene glycol, benzyl alcohol, acetone, butanone, propylene glycol methyl ether acetate, tetrahydrofuran, dimethyl sulfoxide, dichloromethane, chloroform, ethyl acetate, butyl acetate, benzene, toluene, xylene, heptane, n-hexane, cyclohexane and petroleum ether.

[0034] The invention also discloses monodisperse doped titanium dioxide with in-situ lattice strain prepared by the method, and application of the doped titanium dioxide in transparent composite functional materials.

[0035] In an optional application, doped titanium dioxide (prepared by the aforementioned method), methyl methacrylate, polyethylene glycol diacrylate and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide dispersed in a dispersion solvent are fully mixed and then UV-cured in a mold to form a transparent titanium dioxide / acrylate composite material for use as a transparent photochromic display material.

[0036] Compared with the prior art, the present invention has at least the following beneficial effects:

[0037] 1) The doped titanium dioxide with in-situ lattice strain prepared by the method of the present invention is a nano-titanium dioxide with narrow particle size distribution, which has both monodispersity and abundant oxygen vacancies. The titanium dioxide can be monodispersed in a variety of organic solvents, and the particle size distribution can be regulated within the range of 5-100nm by controlling the reaction temperature and the ratio of water to titanium source. The particle size of the product can be reduced by increasing the reaction temperature and reducing the ratio of water to titanium source, and the small particle size sample is further reduced to 10-30nm.

[0038] 2) Due to the secondary introduction of titanium source, the lattice strain at the interface is in situ regulated by relying on the difference in lattice shrinkage rate between the amorphous and crystalline states. While achieving the regulation of oxygen vacancies, the original surface structure and properties of titanium dioxide are retained, avoiding the influence of calcination or other impurity layers on the surface. After surface modification, monodispersity of titanium dioxide is achieved and a high-transparency composite functional material is constructed. The surface modifier can be selected according to different composite systems to ensure the monodispersity performance of titanium dioxide in the corresponding system. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The route and mechanism diagram for preparing monodisperse doped titanium dioxide with in-situ lattice strain;

[0040] Figure 2 This is a physical picture of the product dispersion in Example 2;

[0041] Figure 3 The transmission electron microscope image and geometric phase analysis image of the particles in the dispersion of Example 2;

[0042] Figure 4 is the particle size distribution diagram of the dispersion of Example 2;

[0043] Figure 5 The electron paramagnetic resonance spectra of the unmodified powders in Example 2 and Comparative Examples 1-3 are shown;

[0044] Figure 6 This is a physical picture of the composite film in Example 3. DETAILED DESCRIPTION

[0045] The present invention is further described and illustrated below in conjunction with specific embodiments. The embodiments are merely exemplary of the present disclosure and do not define the scope of limitation. The technical features of each embodiment of the present invention may be combined accordingly without conflicting with each other. Figure 1 The roadmap for synthesizing monodisperse doped titanium dioxide with in-situ lattice strain is presented, and it is shown that at the crystal-amorphous interface, lattice strain will be generated in-situ due to the difference in lattice shrinkage between the two. Specific examples are given below:

[0046] Example 1

[0047] Dissolve 10 mL of isopropyl titanate and 0.15 g of potassium nitrate in 20 mL of ethanol and stir thoroughly until dissolved to form a mixed solution A. Mix 0.8 mL of butyric acid, 0.75 mL of water and 10 mL of ethanol to form a mixed solution B. Add solution B dropwise to solution A under vigorous stirring and mix well. Transfer the above precursor solution to a hydrothermal autoclave. The reaction temperature is 150°C and the reaction time is 24 h.

[0048] After the reaction was completed and cooled, 4 mL of isopropyl titanate and 85 μL of water were added to the reaction solution under stirring, and the solution was transferred to a hydrothermal reactor after being mixed evenly. The heating rate was set to 30 ° C / min, the reaction temperature was 250 ° C, and the reaction time was 2 h. The product was centrifuged at a speed of 6000 rpm, washed with ethanol, and centrifuged three times. 0.5 g of wet solid was added to 10 mL of chloroform, and 0.1 g of dodecyl trimethoxysilane was added, and stirred at 80 ° C for 4 h to form a uniform transparent dispersion.

[0049] Example 2

[0050] Under stirring, 0.2 mL of acetic acid, 0.8 mL of water, 0.18 g of rubidium nitrate, and 6 mL of tetrabutyl titanate were dissolved in 25 mL of benzyl alcohol in sequence. After being fully stirred and mixed, the precursor solution was transferred to a hydrothermal autoclave. The reaction temperature was 200 ° C and the reaction time was 2 h.

[0051] After the reaction was completed and cooled, 1.2 mL of tetrabutyl titanate and 30 μL of water were added to the reaction solution under stirring, and the solution was transferred to a hydrothermal reactor after being mixed evenly, and the heating rate was set to 30°C / min, the reaction temperature was 300°C, and the reaction time was 1h. The product was centrifuged at a speed of 6000 rpm, washed with propylene glycol methyl ether acetate, and centrifuged three times. 1.5 g of wet solid was added to 10 mL of propylene glycol methyl ether acetate, 0.25 g of methoxytriethylene glycol ether propyl trimethoxy silane was added, and stirred at 130°C for 50 min, and then 0.05 g of 3-(acryloyloxy)propyl trimethoxy silane was added, and stirring was continued at 130°C for 10 min to form a uniform transparent dispersion.

[0052] The above dispersion was backwashed and centrifuged, with heptane as the antisolvent and ethyl acetate as the good solvent, and backwashed and centrifuged three times to remove impurities and excess surface modifiers. The wet solid was placed in a vacuum environment for 2 hours to obtain a dry powder. 1 g of the dry powder was dispersed in 10 mL of acetone to obtain a uniform and transparent dispersion. Figure 2 shown.

[0053] The particles in the above dispersion were characterized by transmission electron microscopy (TEM), such as Figure 3As shown in the figure, the particles are evenly distributed and show monodisperse characteristics. At the same time, high-resolution TEM characterization shows that there is an obvious amorphous structure layer on the surface of the particles. Geometric phase analysis shows that there is obvious lattice tensile strain at the amorphous-crystalline interface. The particle size distribution of the product is further tested by a nanoparticle size analyzer, such as Figure 4 As shown, the average particle size of the particles in the dispersion is about 10 nm, and the particle size distribution range is narrow.

[0054] Example 3

[0055] Under stirring, 0.2 mL of butyric acid, 0.8 mL of water, 0.12 g of barium chloride, and 6 mL of tetrabutyl titanate were dissolved in 25 mL of benzyl alcohol in sequence. After being fully stirred and mixed, the precursor solution was transferred to a hydrothermal autoclave. The reaction temperature was 200 ° C and the reaction time was 2 h.

[0056] After the reaction was completed and cooled, 0.6 mL of tetrabutyl titanate and 10 μL of water were added to the reaction solution under stirring, and the solution was transferred to a hydrothermal reactor after being mixed evenly. The heating rate was set to 40 ° C / min, the reaction temperature was 280 ° C, and the reaction time was 2 h. The product was centrifuged at a speed of 6000 rpm, washed with propylene glycol methyl ether acetate, and centrifuged three times. 1.5 g of wet solid was added to 10 mL of propylene glycol methyl ether acetate, and 0.25 g of methoxytriethylene glycol ether propyl trimethoxysilane was added. The mixture was stirred at 130 ° C for 60 min to form a uniform transparent dispersion.

[0057] The above dispersion was backwashed and centrifuged for 3 times with heptane as antisolvent and ethyl acetate as good solvent to remove impurities and excess surface modifier. The wet solid was placed in a vacuum environment for 2 h to obtain a dry powder. 1 g of the dry powder was dispersed in 10 mL of ethanol to obtain a uniform and transparent dispersion.

[0058] Example 4

[0059] Under stirring, 0.5 mL of lactic acid, 0.4 mL of water, 0.18 g of europium nitrate, and 4 mL of titanium tetrachloride were dissolved in 25 mL of octanol in sequence. After being fully stirred and mixed, the precursor solution was transferred to a hydrothermal autoclave. The reaction temperature was 180 ° C and the reaction time was 5 h.

[0060] After the reaction is completed and cooled, 0.5 mL of isopropyl titanate and 10 μL of water are added to the above reaction solution under stirring. After mixing evenly, the above solution is transferred to a hydrothermal reactor, and the heating rate is set to 35 ° C / min, the reaction temperature is 300 ° C, and the reaction time is 1.5 h. The product is centrifuged at a speed of 6000 rpm, washed with ethanol, and centrifuged three times. 1.5 g of wet solid is added to 10 mL of toluene, and 0.25 g of isopropyl tri (dodecylbenzenesulfonyl) titanate is added. Stir for 30 min at 50 ° C to form a uniform and transparent dispersion. Take the above dispersion for backwash centrifugation operation, acetone as the anti-solvent, toluene as the good solvent, and backwash centrifuge 3 times to remove impurities and excess surface modifiers. The wet solid is placed in a vacuum environment for 2 hours to obtain a dry powder. Take 1 g of dry powder and disperse it in 10 mL of toluene to obtain a uniform and transparent dispersion.

[0061] Example 5

[0062] Under stirring, 0.2 g of citric acid, 0.4 mL of water, 0.1 g of aluminum nitrate, and 8 mL of tetrabutyl titanate were dissolved in 30 mL of n-butanol in sequence. After being fully stirred and mixed, the precursor solution was transferred to a hydrothermal autoclave. The reaction temperature was 150 ° C and the reaction time was 24 h.

[0063] After the reaction was completed and cooled, 2 mL of tetraethyl titanate was added to the reaction solution under stirring, and after mixing, the solution was transferred to a hydrothermal reactor, and the heating rate was set to 30 ° C / min, the reaction temperature was 280 ° C, and the reaction time was 1 h. The product was centrifuged at a speed of 6000 rpm, washed with ethanol, and centrifuged three times. 1.5 g of wet solid was added to 10 mL of toluene, 0.18 g of stearic acid was added, and stirred at 60 ° C for 30 min to form a uniform transparent dispersion.

[0064] The above dispersion was backwashed and centrifuged for 3 times, with acetone as the antisolvent and toluene as the good solvent, to remove impurities and excess surface modifiers. The wet solid was placed in a vacuum environment for 2 hours to obtain a dry powder, and 1 g of the dry powder was dispersed in 10 mL of toluene to obtain a uniform and transparent dispersion.

[0065] Example 6

[0066] Under stirring, 0.2 g nitric acid, 0.15 mL water, 0.2 g manganese nitrate, and 8 mL isopropyl titanate were dissolved in 30 mL ethanol in sequence. After being fully stirred and mixed, the precursor solution was transferred to a hydrothermal autoclave. The reaction temperature was 170 ° C and the reaction time was 24 h.

[0067] After the reaction was completed and cooled, 2 mL of isopropyl titanate was added to the reaction solution under stirring, and after mixing, the solution was transferred to a hydrothermal reactor, and the heating rate was set to 40 ° C / min, the reaction temperature was 300 ° C, and the reaction time was 0.5 h. The product was centrifuged at a speed of 6000 rpm, washed with ethanol, and centrifuged three times. 1.5 g of wet solid was added to 10 mL of toluene, and 0.2 g of 9-octadecene-1-ol phosphate was added, and stirred at 100 ° C for 30 min to form a uniform transparent dispersion.

[0068] The above dispersion was backwashed and centrifuged for 3 times, with acetone as the antisolvent and toluene as the good solvent, to remove impurities and excess surface modifiers. The wet solid was placed in a vacuum environment for 2 hours to obtain a dry powder, and 1 g of the dry powder was dispersed in 10 mL of toluene to obtain a uniform and transparent dispersion.

[0069] Comparative Example 1

[0070] Under stirring, 0.2 mL of acetic acid, 0.8 mL of water, 0.18 g of rubidium nitrate, and 6 mL of tetrabutyl titanate were dissolved in 25 mL of benzyl alcohol solution in sequence, and after being fully stirred and mixed, the above precursor solution was transferred to a hydrothermal autoclave, and the reaction temperature was 200 ° C, and the reaction time was 2 h; after cooling, the temperature was raised to 300 ° C at 30 ° C / min, and the reaction was carried out for 1 h. The product was separated by centrifugation at a speed of 6000 rpm, washed with ethanol, and centrifuged three times, and the wet solid was placed in a vacuum environment for 2 h to obtain a dry powder.

[0071] Comparative Example 2

[0072] Under stirring, 0.2mL acetic acid, 0.8mL water, and 6mL tetrabutyl titanate were dissolved in 25mL benzyl alcohol solution in sequence, and after being fully stirred and mixed, the above precursor solution was transferred to a hydrothermal kettle, and the reaction temperature was 200°C and the reaction time was 2h; after the reaction was completed and cooled, 1.2mL tetrabutyl titanate and 30μL water were added to the above reaction solution under stirring, and after mixing, the above solution was transferred to a hydrothermal kettle, and the heating rate was set to 30°C / min, the reaction temperature was 300°C, and the reaction time was 1h. The product was separated by centrifugation at a speed of 6000 rpm, washed with ethanol, and centrifuged 3 times, and the wet solid was placed in a vacuum environment for 2h to obtain a dry powder.

[0073] Comparative Example 3

[0074] Under stirring, 0.2 mL of acetic acid, 0.8 mL of water, and 6 mL of tetrabutyl titanate were dissolved in 25 mL of benzyl alcohol solution in sequence, and after being fully stirred and mixed, the above precursor solution was transferred to a hydrothermal autoclave, and the reaction temperature was 200 ° C, and the reaction time was 2 h; after cooling, the temperature was raised to 300 ° C at 30 ° C / min, and the reaction was carried out for 1 h. The product was separated by centrifugation at a speed of 6000 rpm, washed with ethanol, and centrifuged three times, and the wet solid was placed in a vacuum environment for 2 h to obtain a dry powder.

[0075] The oxygen vacancies of the non-surface-modified samples in Example 2 and the samples in Comparative Examples 1-3 were characterized by electron paramagnetic resonance spectroscopy (EPR). Figure 5 As shown, compared with the samples in Comparative Examples 1-3, the sample in Example 2 under the synergistic effect of in-situ lattice strain and Rb doping has more oxygen vacancies, compared with Example 2, Comparative Example 1 only subjected to doping treatment and Comparative Example 2 only subjected to lattice strain treatment show reduced oxygen vacancy content, and the sample in Comparative Example 3 without lattice strain and doping shows the least oxygen vacancy signal, indicating that both doping treatment and in-situ lattice strain promote the formation of oxygen vacancies.

[0076] Example 7

[0077] Take 5 mL of the dispersion in Example 2, add 1.5 mL of methyl methacrylate, 2.5 mL of polyethylene glycol diacrylate, 0.2 mL of diethylene glycol, 0.4 g of tetrapentaerythritol triacrylate and 35 mg of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, mix well, evaporate the solvent on a heating table at 80°C, and then perform UV curing in a mold to obtain a transparent and uniform titanium dioxide / acrylate composite photochromic film. Figure 6 As shown, the film has high transparency and can change color under ultraviolet light to reduce transparency. Under the action of a photomask, text or patterns can be customized to display on the composite film.

[0078] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing monodisperse doped titanium dioxide with in-situ lattice strain, characterized in that: The steps include: 1) preparing a precursor solution containing a doped metal salt for preparing titanium dioxide, and performing a first solvothermal reaction; 2) adding a titanium source to the reaction solution to conduct a second solvothermal reaction with rapid temperature increase, utilizing the difference in lattice shrinkage at the crystal-amorphous interface to generate lattice strain in situ and reduce the oxygen vacancy formation energy; 3) Centrifuging and washing the reaction product, and performing surface modification on the product using a surface modifier to obtain the monodispersed doped titanium dioxide with in-situ lattice strain.

2. The preparation method according to claim 1, characterized in that: The precursor solution in step 1) includes an organic solvent, water, a doping metal salt, a titanium source and a hydrolysis inhibitor; The organic solvent includes one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, pentanol, hexanol, heptanol, octanol, dodecanol, ethylene glycol, propylene glycol, hexylene glycol, benzyl alcohol, and phenylethyl alcohol; The doping metal salt includes one or more of lithium chloride, sodium chloride, potassium chloride, rubidium chloride, magnesium chloride, barium chloride, copper chloride, manganese chloride, ferric chloride, zinc chloride, tin chloride, aluminum chloride, lithium nitrate, sodium nitrate, potassium nitrate, rubidium nitrate, magnesium nitrate, barium nitrate, copper nitrate, manganese nitrate, ferric nitrate, zinc nitrate, tin nitrate, cerium nitrate, europium nitrate, aluminum nitrate, lanthanum nitrate, terbium nitrate and samarium nitrate; The titanium source includes one or more of titanium tetrachloride, titanyl sulfate, titanium acetylacetonate, tetraethyl titanate, tetrabutyl titanate, isopropyl titanate, titanic acid and metatitanic acid; The hydrolysis inhibitor includes one or more of formic acid, acetic acid, propionic acid, butyric acid, lactic acid, citric acid, tartaric acid, salicylic acid, nitric acid, hydrochloric acid and sulfuric acid; Relative to the organic solvent, the addition amount of the doped metal salt is 0.001-0.03 g / mL, the addition amount of the titanium source is 0.08-0.8 g / mL, and the addition amount of the hydrolysis inhibitor is 0.001-0.05 g / mL; in the precursor solution, the mass ratio of water to the titanium source is 0.02-0.

7.

3. The preparation method according to claim 1, characterized in that: The first solvent thermal reaction temperature in step 1) is 100-230° C., the first solvent thermal reaction pressure is 0.01-5 MPa, and the first solvent thermal reaction time is 0.5-72 h.

4. The preparation method according to claim 1, characterized in that: The titanium source in step 2) includes one or more of titanium tetrachloride, titanyl sulfate, titanium acetylacetonate, tetraethyl titanate, tetrabutyl titanate, isopropyl titanate, titanic acid and metatitanic acid; The molar ratio of the amount of titanium source added in step 2) to the amount of titanium source in the precursor solution in step 1) is 0.05-1; The second solvent thermal reaction temperature is 200-400°C, the second solvent thermal reaction pressure is 0.01-5Mpa, and the second solvent thermal reaction time is 0.5-24h; The second solvent thermal reaction needs to be heated up quickly and kept warm after reaching the desired reaction temperature, with the heating rate being 20-100°C / min.

5. The preparation method according to claim 1, characterized in that: In step 2), while adding the titanium source, an appropriate amount of water is also added to the reaction solution, and the molar ratio of the added water to the titanium source added in step 2) is 0.01-1.

6. The preparation method according to claim 1, characterized in that: The surface modifier described in step 3) includes one or more of titanate, phosphate, organic acid and silane coupling agent; The titanate includes one or more of isopropyl tri(dodecylbenzenesulfonyl) titanate, isopropyl triisostearate titanate, bis(acetylacetonato) diisopropyl titanate, isopropyl tri(dioctylphosphoyloxy) titanate, isopropyl dioleyloxy(dioctylphosphoyloxy) titanate, di(octylphenol polyoxyethylene ether) phosphite and tetraisopropyl di(dioctylphosphite) titanate; The phosphate ester includes one or more of 4-hydroxybutyl dihydrogen phosphate, 2-ethylhexyl dihydrogen phosphate, 9-octadecene-1-ol phosphate, isooctyl phosphate, dodecyl phosphate, tetradecyl phosphate, lauryl alcohol polyoxyethylene ether phosphate and tridecyl polyoxyethylene ether phosphate; The organic acid includes one or more of butyric acid, lactic acid, citric acid, tartaric acid, salicylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, oleic acid, linoleic acid, lauric acid, tetradecanedioic acid, octadecanedioic acid and eicosanedioic acid; The silane coupling agent includes one or more of vinyl trimethoxysilane, vinyl triethoxysilane, octyl trimethoxysilane, octyl triethoxysilane, dodecyl trimethoxysilane, dodecyl triethoxysilane, hexadecyl trimethoxysilane, hexadecyl triethoxysilane, 3-(acryloxy) propyl trimethoxysilane, phenyl trimethoxysilane, γ-aminopropyl trimethoxysilane, 3-glycidyl ether oxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, N-β-aminoethyl-γ-aminopropyl triethoxysilane, methoxy triethylene glycol ether propyl trimethoxysilane, 11-mercapto undecyl trimethoxysilane, 3-mercaptopropyl trimethoxysilane and diethylphosphoethyl triethoxysilane.

7. The preparation method according to claim 1, characterized in that: The centrifugal speed described in step 3) is 3000-8000r / min; The washing solvent is one or more of ethanol, acetone, tetrahydrofuran, propylene glycol methyl ether acetate, toluene and heptane.

8. The preparation method according to claim 1, characterized in that: In step 3), the surface modification process is: adding the washed product and the surface modifier to a reaction solvent to carry out a surface modification reaction at a reaction temperature of 25-150° C. and a reaction time of 0.5-24 h; The mass ratio of the surface modifier to the washed product is 0.05-1; The reaction solvent includes one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, pentanol, hexanol, heptanol, octanol, dodecanol, ethylene glycol, propylene glycol, hexylene glycol, benzyl alcohol, acetone, butanone, propylene glycol methyl ether acetate, tetrahydrofuran, dimethyl sulfoxide, dichloromethane, chloroform, ethyl acetate, butyl acetate, benzene, toluene, xylene, heptane, n-hexane, cyclohexane and petroleum ether.

9. A monodisperse doped titanium dioxide with in-situ lattice strain obtained by the method according to any one of claims 1 to 8.

10. Use of the monodisperse doped titanium dioxide with in-situ lattice strain as claimed in claim 7 in the preparation of transparent composite functional materials.

Citation Information

Patent Citations

  • Preparation method for microemulsion solvent thermosynthesis monodisperse titanium dioxide nanocrystalline

    CN101759228A

  • Preparation method for nano titanium dioxide with high visible light catalytic activity and water dispersion thereof

    CN102180515A

  • TiO2-quantum-dot-and-MoS2-nanometer-flower-combined heterojunction semiconductor material and preparation method thereof

    CN104402052A

  • Anatase type nanometer titanium dioxide, and preparation method and use thereof

    CN109179499A

  • Electrorheological fluid material of titanium dioxide cubic hollow nano particles and preparation method of electrorheological fluid material

    CN110452765A